Health-Related Quality of Life With Trastuzumab Monotherapy Versus Trastuzumab Plus Standard Chemotherapy as Adjuvant Therapy in Older Patients With HER2-Positive Breast Cancer. Issue 22 (1st August 2021) - Taira, Naruto; Sawaki, Masataka; Uemura, Yukari; Saito, Tsuyoshi; Baba, Shinichi; Kobayashi, Kokoro; Kawashima, Hiroaki; Tsuneizumi, Michiko; Sagawa, Noriko; Bando, Hiroko; Takahashi, Masato; Yamaguchi, Miki; et al.
Abstract : PURPOSE: We report findings on quality of life (QoL) in the RESPECT trial, which compared adjuvant trastuzumab monotherapy with trastuzumab plus chemotherapy in older patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer (BC). PATIENTS AND METHODS: Patients age 70-80 years with human epidermal growth factor receptor 2-positive surgically treated breast cancer were randomly assigned to receive trastuzumab (T) or trastuzumab plus chemotherapy (T + C). QoL was assessed using the Functional Assessment of Cancer Therapy-General (FACT-G), Philadelphia Geriatric Center Morale Scale, Hospital Anxiety and Depression Scale, Patient Neurotoxicity Questionnaire, and Tokyo Metropolitan Institute of Gerontology Index of Competence at baseline and after 2, 12, and 36 months. Comparisons were based on individual changes from baseline and were performed by Fisher's test or mixed-model repeated-measures. RESULTS: Among 275 patients in the parent study, 231 (84%) (average age: 74 years) were included in the analysis. At 2, 12, and 36 months, 198, 177, and 178 patients completed surveys, and the mean FACT-G scores at each survey point were 78.9, 80.4, 82.7, and 79.1 in group T and 79.5, 74.5, 78.4, and 78.5 in group T + C. Compared with group T + C, the proportion of patients showing QoL deterioration (≥ 5 points decrease from baseline in FACT-G) was significantly lower at 2 months (31% v 48%; P = .016) and 12 months (19% v 38%; P = .009). In group T, the Hospital Anxiety and Depression Scale score ( P = .003) and the proportion of severe sensory peripheral neuropathy ( P = .001) were significantly lower at 2 months, and Philadelphia Geriatric Center Morale Scale and Tokyo Metropolitan Institute of Gerontology Index of Competence scores were significantly higher ( P = .024, .042) at 12 months. At 36 months, there were no significant differences in any QoL items. CONCLUSION: Detrimental effects of adjuvant chemotherapy on global QoL, morale, and activity capacity lasted for at least 12 months but were not observed at 36 months.